Integration of Steel Slag and Green Compost Enhances Tomato Growth, Physiology, Water use Efficiency, and Antioxidant Responses Under Water-Deficit Stress in Arid Conditions - Farid Errouh; Abdelhamid Aouabe; Lahoucine Ech-Chatir; Nizar El Mazouni; Julio Cesar Rodriguez; Salah Er-Raki; Hassan Chagiri; Hicham Khalisse; Brahim Oudra; Abdelilah Meddich (Journal of Soil Science and Plant Nutrition, 2026)

Enhancing Tomato Yield, Fruit Quality, and Soil Fertility with a Single Application of Steel Slag and Green Waste Compost Across Two Cropping Cycles - Farid Errouh; Abdelhamid Aouabe; Lahoucine Ech-Chatir; Redouane Ouhaddou; Chayma Ikan; Abderrahim Boutasknit; Nizar El Mazouni; Julio Cesar Rodriguez; Salah Er-Raki; Hassan Chagiri; Hicham Khalisse; Brahim Oudra; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Integrated photovoltaic system for rainwater collection and sustainable irrigation - Antonio García-Chica; Angel Mariano Rodriguez-Perez; Julio Jose Caparros-Mancera; Cesar Antonio Rodríguez-Gonzalez; Rosa Maria Chica (Irrigation Science, 2025)
The integration of photovoltaic systems with rainwater harvesting offers a promising solution for enhancing water and energy management in arid and semiarid agricultural regions."This study presents an agrivoltaic system where photovoltaic panels function both as energy source and as surfaces for runoff collection, directing rainwater into a storage reservoir for irrigation. A detailed analysis was conducted to evaluate different scenarios, for a period of ten years, including panel inclination, optimizing at 35°, and the expansion of the photovoltaic field, to enhance energy efficiency and water availability. The results demonstrate that this approach significantly reduces water shortages, reducing critical cases below 50% in first scenario, particularly during peak irrigation demand periods, while increasing the system’s storage capacity and overall resilience to climate variability. The expansion of the photovoltaic system, which is scalable according to the application, demonstrates the overall reduction of critical cases in irrigation availability, increasing the reservoir capacity up to 60,000 m3, which can be combined with increased management of energy generated for the grid, or local generation in remote areas, in combination with improved water supply management. Additionally, the system improves energy sustainability by reducing reliance on external sources and lowering carbon emissions from agricultural activities. The findings highlight the potential of integrating photovoltaic systems into irrigation management as a scalable and replicable framework for enhancing resource efficiency and sustainability in water-scarce regions.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Exploring the potential of hydrolytic enzymes combined with antibacterial agents to disrupt pathogenic biofilms and disinfect released cells - Patricia Palafox-Rivera; Melvin R. Tapia-Rodriguez; Julio Cesar Lopez-Romero; Marco A. Lugo-Flores; Karen P. Quintero-Cabello; Brenda A. Silva-Espinoza; M. Reynaldo Cruz-Valenzuela; Filomena Nazzaro; J. Fernando Ayala-Zavala (Biofouling, 2025)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.